Coordinated Formation of IMPDH2 Cytoophidium in Mouse Oocytes and Granulosa Cells - Ni, Shiwen; Zhang, Teng; Zhou, Chenmin; Long, Min; Hou, Xuan; You, Liji; Li, Hui; Shi, Lanying; Su, You-Qiang (Frontiers in Cell and Developmental Biology, 2021)
Inosine monophosphate dehydrogenase (IMPDH), the rate-limiting enzyme catalyzing de novo biosynthesis of guanine nucleotides, aggregates under certain circumstances into a type of nonmembranous filamentous macrostructure termed “cytoophidium” or "rod and ring" in several types of cells. However, the biological significance and underlying mechanism of IMPDH assembling into cytoophidium remain elusive. In mouse ovaries, IMPDH is reported to be crucial for the maintenance of oocyte–follicle developmental synchrony by providing GTP substrate for granulosa cell natriuretic peptide C/natriuretic peptide receptor 2 (NPPC/NPR2) system to produce cGMP for sustaining oocyte meiotic arrest. Oocytes and the associated somatic cells in the ovary hence render an exciting model system for exploring the functional significance of formation of IMPDH cytoophidium within the cell. We report here that IMPDH2 cytoophidium forms in vivo in the growing oocytes naturally and in vitro in the cumulus-enclosed oocytes treated with IMPDH inhibitor mycophenolic acid (MPA). Inhibition of IMPDH activity in oocytes and preimplantation embryos compromises oocyte meiotic and developmental competences and the development of embryos beyond the 4-cell stage, respectively. IMPDH cytoopidium also forms in vivo in the granulosa cells of the preovulatory follicles after the surge of luteinizing hormone (LH), which coincides with the resumption of oocyte meiosis and the reduction of IMPDH2 protein expression. In cultured COCs, MPA-treatment causes the simultaneous formation of IMPDH cytoopidium in cumulus cells and the resumption of meiosis in oocytes, which is mediated by the MTOR pathway and is prevented by guanosine supplementation. Therefore, our results indicate that cytoophidia do form in the oocytes and granulosa cells at particular stages of development, which may contribute to the oocyte acquisition of meiotic and developmental competences and the induction of meiosis re-initiation by the LH surge, respectively.